Manajemen Komunikasi Islam: Prinsip, Konsep, dan Relevansi di Era Modern - Yudhy Widya Kusumo; Mariana Mariana (Journal of Islamic Management, 2025)
This study aims to explore the relevance of the fundamental principles of Islamic communication in the context of digital communication in the modern era, focusing on the principles of shidiq (truthfulness), amanah (trustworthiness), tabligh (communication), and fathanah (wisdom). The study also discusses the role of Islamic communication management in digital dakwah, along with the challenges and opportunities that arise in spreading Islamic messages through digital platforms. The research method used is a literature review with a qualitative approach, where the researcher examines various relevant sources on Islamic communication principles and their application in modern communication, particularly in the context of social media and information technology. The results show that the principles of Islamic communication play a significant role in maintaining the quality of communication in the digital era. Truthfulness, trustworthiness, and wisdom in communication are crucial in minimizing misinformation, hate speech, and social polarization that often emerge in the online world. Moreover, digital dakwah offers an opportunity to spread Islamic messages in a more inclusive and dynamic manner, but it still requires prudent management to ensure the messages conveyed are accurate and responsible. This study suggests the importance of integrating modern communication theories with Islamic principles to create ethical, harmonious, and constructive communication in the digital world.